Developing Agro-Tourism Tours on the Cocoa Sector in Africa: Emerging Issues from Ghana: Array - Eshun, Gabriel; Tichaawa, Tembi M. (EuroEconomica, 2020)
The need for Africa to diversify its tourism offerings continue to receive research attention. Against this backdrop, this study examined the potential of developing agrotourism, with specific reference to the cocoa sector in Ghana. Ghana has carved a global image for itself as a cocoa production hub. Using a mixed-methodological approach, the study purposively solicited data from respondents in four selected communities that show great potential for cocoa agrotourism business. Semi-structured questionnaires were administered to 120 people selected from the four selected communities. The study also purposively selected and interviewed key informants in the tourism and agriculture sectors. The key findings from the study revealed that cocoa agrotours is a potential avenue to alleviate rural poverty and economic hardships in the country. It must however not be seen as a panacea to rural poverty alleviation. Based on findings, the study concludes that conscious efforts by locals, private and government are needed towards product development, diversification and marketing in the agrotourism niche market.